Effect of Moringa oliefera leaves on feed intake, digestibility, milk production and composition in Friesian cows - Abu El-Hamd, AM; Mohmoud, SA; Elgaml , NB; El-Esawy, GS; Eweedah, N; Sayah, MS; Dawood , R (Journal of the Hellenic Veterinary Medical Society, 2025)
A total of 27 healthy Friesian cows with an average of 540±20.5 kg body weight (BW) was used in this study to investigate the effect of supplemented Moringa oleifera (MO) leaves by different levels on digestibility, milk production and its composition, and feed efficiency of Friesian cows. Cows were divided into three groups and fed a basal ration without supplementation of MO leaves and served as a control group (T1), and supplemented with MO leaves by 40 and 60 g/cow/day in the 2nd group (T2) and the 3rd group (T3), respectively starting from 10 days until 180 days of postpartum. The average daily feed intake was not significant. Cows in T2 and T3 were significantly (P<0.05) higher digestibility coefficients of all parameters compared with T1. Concentrations of protein and albumin in blood plasma were highest significantly and total lipid, cholesterol and urea-N concentrations were lowest significantly with increasing the level of MO leaves in T2 and T3 than in T1. Average daily actual milk yield, 4% fat corrected milk yield (FCMY), fat percentage and fat yield were significantly increased in T3 and T2 compared with T1. Contents of protein, lactose, total solids and solids not fat in milk were not significant. Cows supplemented with 60 g of MO leaves in T3 was significantly the best economic efficiency, followed by T2 and T1. It was determined that feeding 60 g of MO leaves to Friesian cows resulted in better digestibility, blood plasma parameters, milk output and composition, and feed economic efficiency.